(untitled) (Research, Society and Development, 2025)
Hepatitis B is a disease caused by a DNA virus with predominantly sexual transmission, although other routes are also notable for a significant number of cases, such as vertical and parenteral routes - through the use of injectable drugs. The disease is quite prevalent and such exposure, often asymptomatic, favors the chronification process, a serious condition characterized by a clinical condition capable of manifesting, for example, cirrhosis and hepatocellular carcinoma (HCC). In Brazil, the hepatitis B virus (HBV) is present and is responsible for thousands of cases in the country. Therefore, knowing this, the present study aims to analyze the profile of the population affected by hepatitis B in a spatial section of the state of Pernambuco, and temporally, from 2012 to 2020. This analysis was carried out based on information collected from the database secondary data from DATASUS and tabulated in the Microsoft Excel® program. During the period analyzed, 1,719 cases were recorded. The profile of the disease in the state is mainly male, adults (20 to 59 years old), mixed race, residents of the metropolitan region, with completed high school and sexually transmitted. The age group of the population with the most deaths is the elderly. In this sense, it could be concluded that hepatitis B, with high rates in Pernambuco - despite great underreporting -, has a close relationship with age and sexual transmission, despite the existence of vaccination, denoting a lack of knowledge among the population concomitant with a failure of public authorities in carrying out testing and community awareness campaigns.